Review of the Research on the Electricity-Carbon-Hydrogen Coupling Trading Market under the Energy Internet - JIANG Mingxuan, BIAN Yiheng, LI Gengfeng, HUANG Yuxiong, ZHANG Runfan (Dianli jianshe, 2025)
[Objective] In recent times，countries worldwide are actively promoting energy transition and low-carbon development，and the coupling of electricity，carbon，and hydrogen trading has become an inevitable trend in the development of China’s energy industry. However，the complexity of energy mutualization and information interaction across multiple systems is significantly enhanced introducing new challenges to the development of a coupled electricity-carbon-hydrogen trading market. [Methods] This study first introduced the existing research on the electricity-carbon and electricity-hydrogen markets and extensively analyzed the research methodology，coupling mechanism，trading mode，pricing，and clearing mechanism of the electricity-carbon-hydrogen market. Second，because of key challenges at both the physical and information levels that constrain market development，the a framework for the electricity-carbon-hydrogen coupling market within the Energy Internet was proposed to address these issues，along with its participation mechanisms and specific methods. Finally，the study summarized key technologies and research points for the electricity-carbon-hydrogen market from both technical and market levels. [Results] At the physical level，the Energy Internet resolved the electricity-carbon-hydrogen market’s challenge of clarifying the market trading mechanism and decision-making law，which arise due to complexity of resources and interactions. It also established clear laws and mechanisms for energy production and marketing. At the information level，based on information technology and data platforms，the Energy Internet realized data matching and sharing，information transparency，and openness among the electricity，carbon，and hydrogen markets； promoted autonomous and flexible distributed energy trading； and guided the optimal resource allocation. [Conclusions] Exploring the key technologies and research points of the coupled electricity-carbon-hydrogen market for the Energy Internet can overcome the dilemma of the development of the existing market and provide a feasible reference path for improving and developing the construction program of the electricity-carbon-hydrogen market.